การกำจัดสารหนูในรูปอาร์ซิเนตในน้ำเสียสังเคราะห์โดยใช้ไคโตแซนแบบเม็ด - รามนรี เนตรวิเชียร (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The adsorption ability of arsenate from synthetic wastewater using chitosan beads was studied in a completely-mixed batch reactor at room temperature. The results indicated that time, solution pH, initial arsenate concentration, and chitosan weight affected the adsorption capacity. The equilibrium adsorption of arsenate on chitosan beads was reached in less than 24 hours. Arsenate removal efficiency was higher at lower pH. Adsorption capacity of arsenate on chitosan beads was in the range of 0.0061 - 1.3168 mg/g. The appropriate conditions for this study were using chitosan weight of 0.5 grams with shaking rate of 150 rpm at pH 6 for 24 hours. Increasing ionic strength (NaNO3) and the presence of other anion (SO4-2) had no effect on arsenate adsorption on chitosan beads. The result from leaching test for spent chitosan beads showed that arsenate concentration in the solution was less than those of the Ministry of Industry’s standard.